Correlation Equations of Heat Transfer in Nanofluid Al2O3-Water as Cooling Fluid in a Rectangular Sub Channel Based CFD Code - Anwar Ilmar Ramadhan; As Natio Lasman; Anggoro Septilarso (Chemical Engineering Diponegoro University, 2015)
Safety is a major concern in the design, operation and development of a nuclear reactor. One aspect of nuclear reactor safety factor is thermal-hydraulics aspect. In a PWR-type nuclear power plant has been used lighter fluid coolant is water or H2O. In this research, using nanofluid Al2O3-Water with volume fraction of (1%), (2%) and also (3%), used as a cooling fluid in a nuclear reactor core with sub channel PWR fuel element rectangular arrangement. This research was carried out modeling of fuel elements are arranged rectangular, then performed numerical simulations using Computational Fluid Dynamics (CFD) code. In order to obtain the characteristic pattern of flow velocity of each fluid, the fluid temperature distribution along the cylinder wall temperature distribution of the fuel element. Then analyzed the heat transfer in a nuclear reactor core with sub channel PWR fuel element rectangular arrangement, including heat transfer coefficient, Nusselt number (Nu), as well as heat transfer correlations. Heat transfer correlation for nanofluid Al2O3-Water (1%), (2%) and also (3%) proved to core of PWR nuclear reactor fuel element sub channel rectangular arrangement with the Reynolds number (Re) is stretched, namely: 404 096 <Re <423 084 and with constant heat flux is 2600 W / m2, and the composition ratio (pitch / diameter) 1.33.